Information Security and Cryptology - ICISC 2011 14th International Conference, Seoul, Korea, November 30 - December 2, 2011. Revised Selected Papers - Kim, Howon; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed conference proceedings of the 14th International Conference on Information Security and Cryptology, held in Seoul, Korea, in November/December 2011. The 32 revised full papers presented were carefully selected from 126 submissions during two rounds of reviewing. The conference provides a forum for the presentation of new results in research, development, and applications in the field of information security and cryptology. The papers are organized in topical sections on hash function, side channel analysis, public key cryptography, network and mobile security, digital signature, cryptanalysis, efficient implementation, cryptographic application, and cryptographic protocol.
Hash function -- side channel analysis -- public key cryptography.-network and mobile security -- digital signature -- cryptanalysis, efficient implementation, cryptographic application -- cryptographic protocol.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computational complexity; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Systems and Data Security; Discrete Mathematics in Computer Science